Borylation of Arenes with Bis(hexylene glycolato)diboron - Liskey, Carl W.; Hartwig, John F. (Synthesis, 2013)
A series of diolate-substituted diboron compounds were investigated as reagents for iridium-catalyzed C–H borylations of arenes. These studies showed that commercially available bis(hexylene glycolato)diboron reacts with arenes in the presence of the catalyst generated from [Ir(COD)OMe]2 and di-tert-butylbipyridine. This reagent is prepared from a less expensive diol than the more commonly used bis(pinacolato)diboron reagent.
Keywords: iridium; C–H borylation; bis(hexylene glycolato)diboron; arylboronate esters